Interpreting biomedical science : experiment, evidence, and belief - e uthor (London : Academic Press is an imprint of Elsevier, 2015)
Interpreting Biomedical Science: Experiment, Evidence, and Belief discusses what can go wrong in biological science, providing an unbiased view and cohesive understanding of scientific methods, statistics, data interpretation, and scientific ethics that are illustrated with practical examples and real-life applications. Casting a wide net, the reader is exposed to scientific problems and solutions through informed perspectives from history, philosophy, sociology, and the social psychology of science. The book shows the differences and similarities between disciplines and different eras and illustrates the concept that while sound methodology is necessary for the progress of science, we cannot succeed without a right culture of doing things.
4.11 Likelihood as an Unbiased Measure of Evidence4.12 Conclusion: Ideologies Behind Some Methods of Statistical Inference; References; 5 Truth and Belief; 5.1 From Long-Run Error Probabilities to Degrees of Belief; 5.2 Bayes Theorem: What Makes a Rational Being?; 5.3 Testing in the Infinite Hypothesis Space: Bayesian Parameter Estimation; 5.4 All Against All: Bayesianism Versus Frequentism Versus Likelihoodism; 5.5 Bayesianism as a Philosophy; 5.6 Bayesianism and the Progress of Science; 5.7 Conclusion to Part II; References; III. The Big Picture; 6 Interpretation.
Online resource; title from PDF title page (Ebsco, viewed June 19, 2015).
Includes bibliographical references and index.
Keywords: Medicine -- Research -- Methodology; Medical sciences -- Research; MEDICAL -- Research; Medical sciences -- Research; Medicine -- Research -- Methodology; Biomedical Research; Research Design; Philosophy; Electronic books; Electronic books